Civil Liability for Notaries as General Officials and the Role of the Notary Supervisory Board in Unlawful Acts By its Members - Gladys Natalie Aurielle; Mella Ismellina Farma Rahayu (PT Publikasiku Academic Solution, 2024)
This research is entitled Civil liability for Notaries as public officials and the role of the Notary Supervisory Council regarding the legal behavior of its members in making deeds that are not in accordance with the law on notary positions. The results of this research are legal remedies for Notaries who are subject to civil sanctions for unlawful acts and the authority of the Supervisory Council regarding the Notary's legal behavior. The purpose of this research is to analyze the civil liability of Notaries for unlawful acts committed in making authentic deeds and the role of the Supervisory Board in the behavior of its members. The research method used is normative juridical, namely research that focuses on the use of library materials, document studies and interviews